Facile one-step hydrothermal carbonization of coffee husks into activated hydrochar for efficient methylene blue adsorption: Isotherm and kinetic studies - Thi Hien Tran (Center of Biomass & Renewable Energy (CBIORE), 2026)
Recycling agricultural waste into high-performance adsorbent materials represents a sustainable approach for environmentally friendly wastewater treatment, reflecting an important strategy for resource valorization. This study presents an accelerated and simplified route for synthesizing activated hydrochar (AHC) from coffee husks, an abundant lignocellulosic residue. The synthesis employs a one-step hydrothermal carbonization (HTC) under mild conditions (130 °C, 2 h) using 1 mol/L KOH as the activating reagent, followed by pyrolysis. By integrating carbonization and chemical activation into a single HTC stage, the process eliminates the conventional preliminary hydrochar-forming step. It thereby achieves substantial reductions in reaction time and energy input compared with conventional two-stage HTC methods. The resulting AHC exhibits a highly developed microporous architecture, with a BET surface area of 1022.34 m²/g and a surface functionality density of 1.803 mmol/g, both of which contribute to enhanced adsorption performance. Methylene blue adsorption experiments reveal a maximum experimental capacity of 477.43 mg/g, in agreement with the Langmuir monolayer model (Qm = 499.48 mg/g). Kinetic evaluation demonstrates excellent conformity with the pseudo-second-order rate law (R² = 0.9999), indicating rapid and surface-controlled adsorption. The material also retains stable adsorption efficiency over five consecutive regeneration cycles, confirming its robustness and reusability. Collectively, these findings demonstrate that coffee husks constitute a promising precursor for developing efficient adsorbents through a simple, accessible, and energy-efficient one-step HTC strategy. This work provides a practical and sustainable pathway for the valorization of agricultural residues while addressing critical challenges associated with the scalable remediation of dye-contaminated aqueous systems.